Pierre dans l'art belge contemporain (la). - ATELIER 340 (Liège : George Thone, 1983)
Bastianelli, Ariane ; Bockstaele, Herman ; Cauwelier, Willy ; Claus, Christian ; Clemencon, Jean-Pierre ; Cockx, Pol ; Culot, Pierre ; Damoiseaux, Jacques ; Debrabandere, Lieven ; De Kort, Jetje ; Deleu, Luc ; De Middeleer, Dirk ; Desmet, Etienne ; Desomberg, Philippe ; Desrêveux, Frans ; Detilleux, Jean-François ; Dries, Jan ; Feulien, Marc ; Flament, Richard ; Freson, Florence ; Gangolf, Serge ; Gees, Paul ; Germonpre, Gerrit ; Guilmot, Jacques ; Haccuria, Maurice ; Haenen, Toon ; Henrion, Joseph ; Henrotin, Marc ; Holmens, Gerard ; Hubert, Pierre ; Jacquemart, Philippe ; Jacques, Philippe ; Ketele, Alexander ; Kovacs, François ; Croix, Roger La ; Laurent, Philippe ; Lievens, Johan ; Manneback, Alain ; Massart, Jean-Georges ; Martin-Peña, Miguel ; Mathot, Jean ; Meysmans, Willy ; Mouton, Jef ; Navez, Jean-Marc ; Ramon, Renaat ; Roelstraete, Stefaan ; Rohr, Renée ; Roulin, Félix ; Schlüter, Rainer H. ; Smets, Michel ; Smolders, Michel ; Soubry, Bart ; Spilliaert, Pol ; Stroobant, Dominique ; Toussaint, Philippe ; Uytterhoeven, Emiel ; de Kerckhove, Jan Van ; Van den Abeele, Jacques ; Van Droom, Léon ; Van Imschoot, Wannes ; Van Nazareth, Herman ; Van Rafelghem, Pol ; Van Ransbeeck, Bert ; Van Sumere, Hilde ; Verhaeghe, Bernard ; Verhellen, Thierry ; Vermandere, Willem ; Willequet, André ; Willocx, André
Steen in de hedendaagse Belgische kunst 17.6-25.9.1983
boek